2016
DOI: 10.1080/09500839.2016.1257870
|View full text |Cite
|
Sign up to set email alerts
|

Influence of twist boundary on deformation behaviour of 〈1 0 0〉 BCC Fe nanowires

Abstract: Molecular dynamics simulations revealed significant difference in deformation behaviour of <100>BCC Fe nanowires with and without twist boundary. The plastic deformation in perfect <100> BCC Fe nanowire was dominated by twinning and reorientation to <110> followed by further deformation by slip mode. On the contrary, <100> BCC Fe nanowire with a twist boundary deformed by slip at low plastic strains followed by twinning at high strains and absence of full reorientation. The results suggest that the deformation… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 29 publications
2
2
0
Order By: Relevance
“…Similarly, depending on orientation, this potential correctly predicts deformation by twinning and dislocation slip in BCC Fe nanowires 8,9,14,19,20 , which is quite close to the recent experimental observations in ultra-thin BCC W nanopillars 11 . The mechanism of twin nucleation and growth 14,32 , twin boundary as a dislocation source 20,32 , twin migration stress 14,33 , twist boundary structure 34 , accumulation of straight screw dislocations 19 , and various twin-twin interactions 32,33 are in good agreement with those observed experimentally 33,[35][36][37] . BCC Fe nanowires of square cross-section width (d) = 8.5 nm and oriented in <111> axial direction with {110} and {112} side surfaces were created by generating atomic positions corresponding to the bulk Fe.…”
Section: MD Simulation Detailssupporting
confidence: 80%
See 1 more Smart Citation
“…Similarly, depending on orientation, this potential correctly predicts deformation by twinning and dislocation slip in BCC Fe nanowires 8,9,14,19,20 , which is quite close to the recent experimental observations in ultra-thin BCC W nanopillars 11 . The mechanism of twin nucleation and growth 14,32 , twin boundary as a dislocation source 20,32 , twin migration stress 14,33 , twist boundary structure 34 , accumulation of straight screw dislocations 19 , and various twin-twin interactions 32,33 are in good agreement with those observed experimentally 33,[35][36][37] . BCC Fe nanowires of square cross-section width (d) = 8.5 nm and oriented in <111> axial direction with {110} and {112} side surfaces were created by generating atomic positions corresponding to the bulk Fe.…”
Section: MD Simulation Detailssupporting
confidence: 80%
“…Since the nanowire surfaces can act as local stress raisers, it is reasonable to conclude that the surfaces of the nanowires/nanopillars provide a source for the dissociation of immobile dislocations in BCC nanowires. The dissociation of <100> screw dislocation has also been observed at the twist boundary of BCC Fe and it has been shown that the surfaces aid to the dissociation 34 . In BCC/FCC metallic nanowires, the variations in yield stress (σ Y ) with temperature (T) follow either σ Y = A−BT or σ Y = A−B √ T relation depending upon the inter-atomic potential used in MD simulations 6,46 .…”
Section: Dislocation Multiplication Mechanism and Dissociation Of Imm...mentioning
confidence: 95%
“…It has been shown that in samples free of initial defects, the twinning is inherently favoured at low temperatures and high strain rates [25]. However, the presence of initial dislocations may change the deformation mode from twinning to dislocation slip [25,26]. The occurrence of twinning under tensile loading in <100> BCC Fe nanowires is in agreement with earlier MD simulation studies [13,14,17] and experimental obser-vations on BCC W nanowires of size 15 nm [18].…”
Section: Resultssupporting
confidence: 86%
“…With increasing strain, this reoriented nanowire undergoes deformation by slip, but this has not lead to diffused necking and as a result, the pentagonal atomic chains were not observed. Detailed studies on <100> BCC Fe nanowires have shown that the deformation by twinning followed by reorientation occurs at 10 K [27][28][29] . This result shows that the orientation nanowire also influence the formation of pentagonal atomic chains in BCC Fe nanowires.…”
Section: Resultsmentioning
confidence: 99%